Kyrgyz Republic : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2012)
The paper focuses on the workings of the Medium-Term Development Program (MTDP) of the Kyrgyz Republic. Raising living standards as well as taking measures for reducing poverty have been cited as the main priority areas of the strategy, and the measures to be undertaken to bring about improvements in these areas are highlighted. The report also throws light on the major objectives of MTDP's three-year strategy during the period from 2012-14.